Adherence to infliximab therapy in inflammatory bowel disease patients in a real‐life setting. Issue 10 (27th November 2017) - Martelli, Laura; Lopez, Anthony; Strobel, Sophie; Danese, Silvio; Roblin, Xavier; Baumann, Cédric; Peyrin‐Biroulet, Laurent
Abstract : OBJECTIVE: To assess adherence to infliximab (IFX) therapy in inflammatory bowel disease patients, to investigate reasons for non‐adherence and to identify predictors for non‐adherence. METHODS: This observational study was conducted in two French referral university hospitals between 1 September and 31 October, 2011. Patients were systematically asked if they had already delayed or missed an IFX perfusion since the beginning of the treatment and about the reasons for their non‐adherence. RESULTS: Of the 162 included patients (121 Crohn's disease [CD], 41 ulcerative colitis), 87 (53.7%) reported a delay of at least one IFX injection and 14 (8.6%) missed at least one IFX perfusion since the beginning of the treatment. The overall non‐adherence rate was 54.3%. Pooling all misses, the main reasons for non‐adherence were pregnancy (33.3%), intentional non‐adherence (20%) and forgetfulness (13.3%). Pooling all delays, the main reasons for non‐adherence were professional constraints (46.9%), infections (17.3%) and travels (14.3%). Perineal disease was associated with IFX delays ( P = 0.0007, odds ratio 4.0), whereas active CD/UC was associated with IFX misses ( P = 0.0258, OR = 5.4). CONCLUSIONS: The overall non‐adherence rate for IFX use was 54.3%. Professional constraints and intentional non‐adherence were the leading causes of non‐adherence. Perineal disease and active CD were negatively related to adherence.